Association between dry eye disease and depression: An umbrella review - Ching-Yao Tsai; Ching-Yao Tsai; Ching-Yao Tsai; Ching-Yao Tsai; Zhu Liduzi Jiesisibieke; Tao-Hsin Tung (Frontiers Media S.A., 2022)
PurposeThis umbrella review aimed to summarize the available evidence on the association between dry eye disease and depression.MethodsWe searched the Pubmed, Embase, and Cochrane databases using the search string "(Dry eye syndrome OR Keratoconjunctivitis sicca OR KCS OR Aqueous tear deficiency OR Sjogren syndrome) AND (depression OR depressive symptoms) AND (meta-analysis OR systematic review)" from inception to 20 July 2022. We considered all meta-analyses investigating the association between dry eye disease and depression.ResultsAfter summarizing the included meta-analyses, it was concluded that dry eye disease is associated with depression. The symptoms of dry eye disease affect the daily lives of patients, thus affecting their mood. However, further evidence is required to confirm this association.ConclusionThis finding highlights the importance of psychological support for patients with dry eye disease. Future clinical studies should investigate the mechanism underlying the association between dry eye disease and depression.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022320619.